S M Nazmuz Sakib’s Hypothesis of Aerosol-Sea Ice Feedback: Implications for Climate System Dynamics - Sakib, S M Nazmuz (Asian Pacific Journal of Environment and Cancer, 2023)
This research paper explores S M Nazmuz Sakib’s hypothesis of aerosol-sea ice feedback and its implications for climate system dynamics. The hypothesis suggests that changes in aerosol emissions significantly impact sea ice concentration and thickness in the Arctic, which, in turn, affect aerosol transport and deposition over the Tibetan Plateau. The paper presents a comprehensive analysis of the hypothesis, including the underlying facts, a proposed formula for the aerosol-sea ice feedback, and the potential variations of this feedback based on regional and temporal patterns of aerosol emission changes. Furthermore, the paper introduces the Sea Ice-Aerosol-Cloud Feedback (SIACF) Index and its application to historical incidents related to aerosol emission changes. The SIACF Index provides a quantitative measure to evaluate the influence of changes in aerosol emissions on sea ice concentration and thickness. The paper concludes by emphasizing the importance of testing this hypothesis through global aerosol models, observations, and historical incidents to gain a deeper understanding of aerosol-climate interactions and develop effective mitigation strategies.